INVESTIGATING STUDENTS’ EFFORT IN SUCCEED IN SPEAKING ENGLISH: A CASE STUDY ON STUDENTS’ PERSPECTIVE - Lina Anisah; La Ode Muhammad Idrus Hamid B (Lingua, 2023)
Abstract: This research was conducted to investigate the students’ efforts in speaking skills and the aspects of speaking skill that mostly developed by the students at the seond grade of SMAN 1 Mowewe. This research used a descriptive qualitative method by using case study English design. In conducting this research, the researcher took class XI MIA 1 of SMAN 1 Mowewe as a subject of the research with considerable that the class have the highest effort to improve speaking skill. The researcher used two kinds of instrument, namely questionnaire and interview. The researcher analyzed the data of the questionnaire by calculating and analyzing the students’ answer. For the interview the researcher used transcribing the tape recording, coding (labeling) the whole transcribed text, seeking for and naming the themes, reviewing the themes to make sure they fit the data, and the write-up (creating a coherent narrative). The result of this research showed that the students had six activities of students’ efforts in speaking skill. There were 1) students used the new vocabulary in speaking for easily remember the vocabulary, 2) students used mirror in speaking English fluently, 3) students checked the correct pronunciation on an online dictionary, 4) students asked a friend for helping them if they forgot the vocabulary, 5) students looked for the native speakers in improving their pronunciation, and 6) students made a small note to write the new vocabulary. In additional the interview data showed that there were some aspects of the speaking skill, namely vocabulary, comprehension, fluency, pronunciation, and grammar. Then the researcher got information from the interview about the aspect of speaking skill that mostly developed by the students is vocabulary. There were 4 students from 5 students chose vocabulary as an aspect that mostly developed by the students